Allergen immunotherapy during the COVID‐19 pandemic—A survey of the German Society for Allergy and Clinical Immunology. Issue 3 (28th March 2022) - Pfaar, Oliver; Hamelmann, Eckard; Klimek, Ludger; Taube, Christian; Vogelberg, Christian; Wagenmann, Martin; Werfel, Thomas; Worm, Margitta
Abstract: Background: When the coronavirus pandemic 2019 (COVID‐19) emerged, concerns were also raised regarding the safety of allergen immunotherapy (AIT). The German Society for Allergology and Clinical Immunology (DGAKI) conducted a survey to collect real‐world data on the daily routine of administering subcutaneous AIT (SCIT) and sublingual AIT (SLIT) during the COVID‐19 pandemic. Methods: A web‐based retrospective survey using the online platform survio with 26 standardized questions was used to survey physicians treating allergic patients during the pandemic. Results: Three hundred and forty‐five physicians who regularly offer and perform AIT in German‐speaking countries responded to the questions. 70.4% of the respondents stated that they regularly initiated and dosed up SCIT for inhalant allergies (41.4% venom‐SCIT, 73.6% SLIT), and 85.2% of the respondents stated that they continued SCIT for inhalant allergies during the maintenance phase in a regular way (59.1% venom‐SCIT, 90.4% SLIT) in healthy patients without current symptoms indicating an infection with COVID‐19. With regard to tolerability, there was no evidence for increased occurrence of adverse events in patients without current symptoms of COVID‐19 infection during the pandemic. Conclusions: This retrospective study demonstrated adherence to national and international position papers of AIT during the COVID‐19 pandemic in German‐speaking countries. Besides, the survey has confirmed a good tolerability of AIT for both SCIT and SLIT.